The influence of dental beliefs on pediatric dentistry treatment - Strieder, Anna Paola (2019)
Health beliefs have often been related to the increase of dental fear and anxiety. Such beliefs are strongly influenced by lay knowledge built on the basis of opinions and publications found in mass media. This study was divided in two phases, aiming to (1) produce evidence based on a systematic meta-analytic review of the relationship between negative beliefs and dental fear/anxiety, and (2) to evaluate the interests of Google users on the use of amber necklaces to alleviate teething symptoms in children from different countries. In the first phase, observational studies were retrieved by Cochrane, Embase Search, Portal da BVS, Clinical Trials, Ovid, Open Grain, PubMed, Scopus and Web of Science, and were manually checked for inclusion of additional articles of interest. The quality evaluation of the studies was performed by applying three different versions of the Newcastle-Ottawa Scale, for cohort, case-control and cross-sectional studies. Only studies with low or moderate risk of bias contributed to meta-analysis. In the second phase, computational metadata related to the amber necklace generated from the activity of Google users of 17 countries were collected from the tool Google Trends. Four search strategies were defined in English, Spanish, Portuguese and Italian to retrieve the monthly variation of the Relative Search Volume (RSV) between January 2004 and September 2018, including all categories and sources of search. The trends of interests and their respective 12-month predictive models were constructed by ARIMA models, and monthly and quarterly seasonal influences by generalized additive models (GAM). Values of P<0.05 were considered significant. Based on these results, the presence of negative beliefs in health was directly related to the increase of dental fear and anxiety; however, these findings are supported in studies with unclear/moderate risk of bias. Regarding the interests on amber necklace, RSV curves were characterized by upward trends in most studied countries over the years, without the influence of seasonality. The queries were often associated with the desire for additional information, regarding the definition, usability and relief of symptoms caused by amber jewelries. In conclusion, negative health beliefs are directly related to the increase of dental fear and anxiety. Also, the results indicate an increasing interest of Google users in topics related to the amber necklace. In this sense, Internet activity can be used as an important source of data to monitor the beliefs and behaviors of different populations, aiding policy makers and dental service providers to develop and implement interventions focused on the needs and safety of health seekers.